2018
DOI: 10.1007/s10858-018-0200-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving yields of deuterated, methyl labeled protein by growing in H2O

Abstract: Solution NMR continues to make strides in addressing protein systems of significant size and complexity. A fundamental requirement to fully exploit the N-H TROSY and C-H methyl TROSY effects is highly deuterated protein. Unfortunately, traditional overexpression in Escherichia coli (E. coli) during growth on media prepared in DO leads to many difficulties and limitations, such as cell toxicity, decreased yield, and the need to unfold or destabilize proteins for back exchange of amide protons. These issues are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Therefore, our findings could be more general and subsequently extended to other bacterial cell growing protocols. For example, Wand and co-workers have described a method utilizing drop-out deuterated algal lysate (lacking isoleucine, leucine, and valine) for the production of highly deuterated, side chain methyl group labeled proteins in protonated medium (O'Brien et al 2018). While that described procedure utilized 1.5x buffered minimal media and produced substantial gains, our results suggest that even higher yields could be achieved with 2x buffered media.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Therefore, our findings could be more general and subsequently extended to other bacterial cell growing protocols. For example, Wand and co-workers have described a method utilizing drop-out deuterated algal lysate (lacking isoleucine, leucine, and valine) for the production of highly deuterated, side chain methyl group labeled proteins in protonated medium (O'Brien et al 2018). While that described procedure utilized 1.5x buffered minimal media and produced substantial gains, our results suggest that even higher yields could be achieved with 2x buffered media.…”
Section: Discussionmentioning
confidence: 75%
“…Early examples of acclimatizing bacteria include growing cells on agar plates or in liquid culture with increasing ratios of D 2 O:H 2 O (Venters et al 1995;Gardner and Kay 1998). Recently, several reports have appeared describing new methods for increasing protein yield using higher cell densities, fermentation techniques, or amino acid drop-out algae lysate supplements (Cai et al 2016;O'Brien et al 2018;Klopp et al 2018). Whereas impressive gains in protein expression are noted in each, many of these methods require special equipment (e.g., fermenters) and none are as simple as the typical minimal media and methods for heterologous protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has found that commercial protein refolding kits can greatly accelerate the identification of refolding conditions, even for large multi-domain proteins. More recently, we have developed a protocol for expression of proteins in E. coli during growth on H 2 O that results in extensive deuteration and does not require back-exchange (O’Brien, Lin, Fuglestad, Stetz, Gosse, Tommos et al, 2018). For quantitative backbone dynamics experiments, labeling schemes that place 13 C adjacent to amide 15 N should be avoided.…”
Section: Nmr Spin Relaxation Methodsmentioning
confidence: 99%
“…d -amino acids may also inhibit bacterial growth at high concentrations (Hishinuma et al 1969 ; Bardaweel 2014 ). It was also noted that during growth on deuterated amino acid media (O’Brien et al 2018 ; Fiaux et al 2004 ), exchange of amide moieties occurs, but results in only 10–50% incorporation of alpha protons for hydrophobic residues (Löhr et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%